Characterizing the radio continuum nature of sources in the massive star-forming region W75N (B). Issue 3 (20th June 2020) - Rodríguez-Kamenetzky, A; Carrasco-González, C; Torrelles, J M; Vlemmings, W H T; Rodríguez, L F; Surcis, G; Gómez, J F; Cantó, J; Goddi, C; Kim, J S; Kim, S -W; Añez-López, N; et al.
ABSTRACT: The massive star-forming region W75N (B) is thought to host a cluster of massive protostars (VLA 1, VLA 2, and VLA 3) undergoing different evolutionary stages. In this work, we present radio continuum data with the highest sensitivity and angular resolution obtained to date in this region, using the VLA-A and covering a wide range of frequencies (4–48 GHz), which allowed us to study the morphology and the nature of the emission of the different radio continuum sources. We also performed complementary studies with multi-epoch Very Large Array (VLA) data and Atacama Large Millimeter Array (ALMA) archive data at 1.3 mm wavelength. We find that VLA 1 is driving a thermal radio jet at scales of ≈0.1 arcsec (≈130 au), but also shows signs of an incipient hypercompact H ii region at scales of ≲1 arcsec (≲1300 au). VLA 3 is also driving a thermal radio jet at scales of a few tenths of arcsec (few hundred of au). We conclude that this jet is shock exciting the radio continuum sources Bc and VLA 4 (obscured Herbig–Haro objects), which show proper motions moving outward from VLA 3 at velocities of ≈112–118 km s −1 . We have also detected three new weak radio continuum sources, two of them associated with millimetre continuum cores observed with ALMA, suggesting that these two sources are also embedded young stellar objects in this massive star-forming region.